The Accidental Systems Librarian - Singer-Gordon, Rachel (Information Today Inc, 2012)
Here is a book that fills in part of a gap in librarianship education--the business of running a library, especially the machinery and software that make a modern library possible. It is full of encouragement and suggestions for keeping up with the realities of continual learning about computers, networking, software, security, databases, instruction and training, and record keeping.